Innovation of environmental management system as prototype of eco-temple models in Nakohon Pathom Province, Thailand - Wichai, Phra Jaroenphong; Sutnato, Phra Maha Narongsak; Thanomwaro, Phra Maha Thanom; Seankheankaew, Pattamawadee; Ketsil, Tanet (Edelweiss Applied Science and Technology, 2025)
The research entitled “Innovation of Environmental Management System in Temples as a Prototype of Eco-Temple Models in Nakhon Pathom Province, Thailand” has three objectives: 1) to study the design of environmental management systems in temples, 2) to develop activities to drive the environmental management system, and 3) to evaluate the environmental management system of temples as eco-temple models in Nakhon Pathom Province. This mixed-methods investigation examined the development and implementation of sustainable environmental management systems in temples as localized contributions to Sustainable Development Goals (SDGs) 11 (Sustainable Cities and Communities), 12 (Responsible Consumption and Production), and 13 (Climate Action). Results revealed three significant findings: (1) effective environmental management systems demonstrated five interdependent structural components; (2) environmental management intervention activities were developed and implemented across four dimensions; and (3) evaluation metrics demonstrated high overall implementation efficacy (M=3.72), with environmental policy formulation achieving the highest performance indicators (M=3.77), followed by strategic planning processes (M=3.70). Assessment utilizing the GREEN principles framework indicated satisfactory performance in waste management systems, sanitation facilities, nutritional practices, energy utilization, and environmental protection measures. The research culminated in the development of the "GREEN TEMPLE Model,” which consists of two complementary components: (1) the GREEN operational framework focusing on five critical intervention areas—garbage, restrooms, energy, environment, and nutrition—enabling systematic approaches to environmental challenges within institutional boundaries; and (2) the TEMPLE conceptual framework emphasizing six foundational elements: temple, environmental management, participation, learning, and energy. These elements are grounded in the Apassena principle (virtues to lean on), providing a decision-making framework for sustainability initiatives, and reinforced by the Sappāya principle (seven favorable conditions), establishing a holistic approach to environmental development in religious institutions.